Evaluating the performance of HIV testing in infants exposed to antiretroviral prophylaxis within South Africa’s prevention of mother to child transmission programme - Sherman, Gayle (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.